Fukushima accident : 10 years after - Povinec, P.; Hirose, Katsumi; Aoyama, Michio, 1953-2022; Tateda, Yutaka (Elsevier, 2021)
Fukushima Accident: 10 Years After evaluates the post-Fukushima accident situation with up-to-date information, emphasizing radionuclide impacts on the terrestrial and marine environments, and comparing them to the pre-Fukushima accident levels of radionuclides in the environment. This is based on scientific results, as well as knowledge gathered from literature to provide current information on the present status, summarize 10 years of data on the Fukushima accident, and describe the present situation in the local, regional, and global time and space scales. It provides data on radioactivity released into the atmosphere and the ocean, the distribution of radionuclides in the world atmosphere and oceans, and their impact on the total environment, including assessments of radiation doses in Japanese and world populations from consumption of terrestrial food and seafood. It goes on to describe future aspects of the radioactive contamination of these environments and the health implications. This book informs environmental scientists, academics, and researchers in environmental science and nuclear energy as well as postgraduate students in the field of environmental science, radioactivity, and nuclear energy, on the present situation of radioactive contamination of Japan and in the world.